2020
DOI: 10.22317/jcms.v6i2.743
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation esthetic and functional outcomes after rhinoplasty

Abstract: Objective: The aim of this study was to determine patient satisfaction in regard to nose appearance and function with the use of a validated questionnaire, before and after rhinoplasty surgery. Methods: A prospective study was conducted of all adult patients that underwent open rhinoplasty including other nasal procedures like septoplasty or turbinoplasty between September 2018 and August 2019 in both public and private hospital (Sulaimani Surgical Teaching Hospital and Faruk Medical City).The Rhinoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…As it is known, most aesthetic Rhinoplasty participants of the study were female this is ongoing with Zanyar and his colleague's study which demonstrated that majority of Rhinoplasty candidates are females as they are more concerned about their facial appearance [16]. Regarding educational level, study disclosed that mostly had a bachelor's which is also similar with an epidemiological study conducted to Kazemy and his colleagues [14].…”
Section: Discussionsupporting
confidence: 69%
“…As it is known, most aesthetic Rhinoplasty participants of the study were female this is ongoing with Zanyar and his colleague's study which demonstrated that majority of Rhinoplasty candidates are females as they are more concerned about their facial appearance [16]. Regarding educational level, study disclosed that mostly had a bachelor's which is also similar with an epidemiological study conducted to Kazemy and his colleagues [14].…”
Section: Discussionsupporting
confidence: 69%